INTEGRASI TAZKIYATUN NAFS DALAM PENDEKATAN KONSELING ISLAM UNTUK MENINGKATKAN GROWTH MINDSET - Nadya Rostiani; Nabiila Zahra; Yessy Nurfadillah; Agus Sukirno (STKIP Subang, 2026)
This study aims to analyze the integration of the concept of tazkiyatun nafs within the Islamic counseling approach as an effort to enhance individuals’ growth mindset. Tazkiyatun nafs is understood as a process of self-purification that emphasizes self-control, moral development, and strengthening closeness to Allah SWT. Meanwhile, a growth mindset refers to a way of thinking that believes an individual’s abilities can be developed through effort, learning processes, and perseverance in facing various challenges. The method employed in this study is a literature review by examining various relevant sources related to Islamic counseling, the concept of tazkiyatun nafs, and growth mindset theory.The findings indicate that the implementation of tazkiyatun nafs in Islamic counseling can be carried out through several techniques, such as muhasabah (self-reflection), repentance (taubat), remembrance of Allah (dzikir), and the reinforcement of spiritual values that encourage individuals to develop optimism, patience, and perseverance. These values are aligned with the characteristics of a growth mindset, including belief in the process, the ability to learn from failure, and the motivation to continuously improve. Therefore, the Islamic counseling approach that integrates tazkiyatun nafs not only functions to address psychological problems but also contributes to shaping a growth-oriented mindset grounded in spiritual values.